Assessing the impact of an educational intervention program based on the theory of planned behavior on the nutritional behaviors of adolescents and young adults with PCOS in Iran: a field trial study - Leila Hajivandi; Mahnaz Noroozi; Firoozeh Mostafavi; Maryam Ekramzadeh (BMC, 2021)
Abstract Background Polycystic ovary syndrome is the most common endocrine disorder among adolescents and adults. Given the importance of healthy nutritional behaviors in management of this disease, the present study was conducted to determine the impact of an educational intervention program based on the theory of planned behavior on the nutritional behaviors of adolescents and young adults with polycystic ovary syndrome. Methods In this field trial study, 72 participants aged between 15 and 21 years old from four gynecology clinics in Shiraz, Iran, were assigned into the intervention and control groups. Educational intervention program was implemented based on the theory of planned behavior over 4 sessions during two weeks. The data collection tools were researcher-made questionnaires of demographic information, knowledge assessment, and assessment of theory of planned behavior constructs, as well as a questionnaire for assessing consumption of food groups, fast food, and snacks. The data were collected at two stages (once at baseline and once three months after the intervention), and then the changes in knowledge, attitude, subjective norms, the perceived behavioral control, behavioral intention, and nutritional behavior were analyzed using descriptive and inferential statistical methods (t-test, Chi-square, Mann- Whitney U, and Wilcoxon tests; as well as one- way ANOVA, repeated measures ANOVA, and ANCOVA, respectively). Results Statistically significant increases were observed in the mean scores of knowledge, attitude, subjective norms, the perceived behavioral control, behavioral intention, and nutritional behavior in the intervention group by passing three months from the intervention compared to the scores before the intervention (P < 0.001). However, these differences were not statistically significant in the control group (P > 0.05). Moreover, the mean scores of knowledge, attitude, subjective norms, perceived behavioral control, behavioral intention, and nutritional behavior had no statistically significant difference before the intervention between the two groups; however, this was statistically significant by passing three months from the intervention (P < 0.001). Conclusion Considering the effect of an educational intervention program based on the theory of planned behavior on creating healthy nutritional behaviors in adolescents and young adults with polycystic ovary syndrome, it is recommended to use it in order to improve the nutritional health of them. Trial registration: IRCT, IRCT20160224026756N6. Registered 18 Aug 2018, https://en.irct.ir/user/trial/32693/view